PROSPECTIVE WAYS OF DEVELOPMENT OF TOURIST AND RECREATIONAL POTENTIAL OF LVIV REGION, UKRAINE - Oksana BEREZIVSKA; Zinoviy BEREZIVSKYY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Theoretical bases and methodical approaches to the study of the state of tourist and recreational potential of Lviv region are substantiated and the main tendencies of its changes for the future are determined. Many of the problems associated with the development of the tourism industry remain unexplored and need further elaboration. This testifies to the relevance and expediency of further research. The method of research of the state of tourist and recreational potential of Lviv region, which is based on the use of a number of general scientific methods, is described. The tendencies of development of tourist and recreational potential of Lviv region are substantiated. Wide range of different types of tourism is developing in the Lviv region now and therefore there is a well-developed network of enterprises that serve the tourism industry. The available strong tourist and recreational potential indicates that the development of the tourism industry has become one of the most priority economic directions of Lviv region. According to the results of the study, the relevant conclusions are given.